Spontaneous coronary artery dissection – rare but challenging - Putniković, Biljana; Ilić, Ivan; Panić, Miloš; Aleksić, Aleksandar; VIdaković, Radosav; Nešković, Aleksandar N. (Vojnosanitetski pregled, 2014)
Introduction. Spontaneous coronary artery dissection (SCAD) is a rare cause of the acute coronary syndrome. It occurs mostly in patients without atherosclerotic coronary artery disease, carrying fairly high early mortality rate. The treatment of choice (interventional, surgical, or medical) for this serious condition is not well-defined. Case report. A 41-year old woman was admitted to our hospital after the initial, unsuccessful thrombolytic treatment for anterior myocardial infarction administered in a local hospital without cardiac catheterization laboratory. Immediate coronary angiography showed spontaneous coronary dissection of the left main and left anterior descending coronary artery. Follow-up coronary angiography performed 5 days after, showed extension of the dissection into the circumflex artery. Because of preserved coronary blood flow (thrombolysis in myocardial infarction – TIMI II-III), and the absence of angina and heart failure symptoms, the patient was treated medicaly with dual antiplatelet therapy, a low molecular weight heparin, a beta-blocker, an angiotensin-converting enzyme (ACE) inhibitor and a statin. The patient was discharged after 12 days. On follow-up visits after 6 months and 2 years, the patient was asymptomatic, and coronary angiography showed the persistence of dissection with preserved coronary blood flow. Conclusion. Immediate coronary angiography is necessary to assess the coronary anatomy and extent of SCAD.  In patients free of angina or heart failure symptoms, with preserved coronary artery blood flow, medical therapy is a viable option. Further evidence is needed to clarify optimal treatment strategy for this rare cause of acute coronary syndrome.
Keywords: acute coronary syndrome; dissection; coronary angiography; diagnosis; treatment outcome